Pterocryptis subrisa, a new silurid catfish (Teleostei: Siluridae) from northeastern India - Ng, Heok Hee; Lalramliana, Lalramliana; Lalronunga, Samuel (Zootaxa, 2018)
Pterocryptis subrisa, a new species of silurid catfish from the Kaladan River drainage in northeastern India, is described in this study. It can be distinguished from congeners by the unique combination of the following characters: supralabial fold extending posteriorly beyond vertical through posterior orbital margin; nearly circular eye; head length 17.6–19.6% SL; head depth 10.6–11.9% SL; dorsal-fin height 2.6–4.7% SL; 2 dorsal-fin rays; pectoral-fin length 11.8–14.0% SL; body depth at anus 14.4–16.7% SL; caudal peduncle depth 6.8–8.5% SL; 66–75 anal-fin rays; confluent anal and caudal fins separated by deep notch; 17 principal caudal-fin rays; and 57 vertebrae. The generic status of Pterocryptis taytayensis is discussed, with this species being reassigned to Ompok.